Reading, Encoding, Annotating, Pondering (REAP) As a Teaching Reading Strategy to Improve Students Reading Comprehension at The Tenth Grade of SMK Negeri 1 Dobo - Oraile, Orpa Penina; Lekawael, Rosina F. J.; Binnendyk, Sophia (Indonesian Research Journal on Education, 2021)
This study aims to enhance students' reading comprehension through the Reading, Encoding, Annotating, Pondering (REAP) strategy using a classroom action research (CAR) methodology. Conducted with grade X-TPM students from SMK N 1 Dobo during the 2020/2021 academic year, the research involved 11 students over three cycles, each comprising planning, action, observation, and reflection. Data collection included pre-tests, post-tests, observation checklists, and student questionnaires. The study addressed two research questions: 1) How does the REAP method improve reading comprehension for tenth-grade students at SMK Negeri 1 Dobo? 2) What are the pros and cons of using REAP for teaching reading? Improvements in test scores measured success. The findings showed a marked enhancement in reading comprehension, with progressive score improvements across the cycles. Initially, only 2 students had good scores, but by the third cycle, all students scored between 70 and 95, meeting the success criteria and demonstrating significant improvement with the REAP strategy.